Mellan domesticering och exotisering. Kulturreferenser i äldre och nyare översättningar av Maj Sjöwalls och Per Wahlöös kriminalromaner till polska - Pietrzak-Porwisz, Grażyna (Folia Scandinavica Posnaniensia, 2015)
The present paper deals with culture-specific items as a translational problem. It is based on two Polish translations of four Swedish books from the famous detective series by Maj Sjöwall and Per Wahlöö. The aim of the study is to analyze some of the practices employed by two Polish translators against the translation methods proposed by Newmark (1988), Svane (2002) and Ingo (2009). For this purpose a number of highly specific cultural items have been collected and the methods applied by translators have been identified. The analysis has shown a big difference between translators in dealing with culture-specific items. The first translator, Maria Olszańska, adopts such translation methods as calque translation, hyperonym, functional equivalent, paraphrase and omission. The other translator, Halina Thylwe, prefers transference and calque translation combined with additional explanations, either in the main part of the text or in footnotes. The methods employed by both translators are a result of choosing between global translation strategies domestication and foreignization (Venuti 1995). Domestication, adopted in the older translations, minimizes the strangeness of the Swedish text to the Polish readers, whereas foreignization in the newer translations retains the foreignness of the original.